Uso y Difusión de Normas Técnicas Relacionadas con Sistemas de Gestión en el Sector de Elaboración de Productos Alimenticios y de Bebidas - Hernández Riaño, Helman Enrique; Lancheros Suárez, Valery José; Robles González, Juana Raquel (Ingeniería, 2007)
The present organizations are put under demanding requirements of groups of interest as they are it clients, nongovernmental communities, organizations, employees, etc. This introduces new subjects of much relevance for the form in which the organizations are managed, such as the management of the quality, the environmental management, the management of the industrial security and the occupational health, etc. These aspects, as strategic resources of the management must be managed [1], for which arise diverse organizational theories that they look for to explain and to predict the results that certain managemental practices will have in the fulfillment of the requirements of the interest groups. The use and implementation of management systems are a key aspect for the competitiveness of the companies, since it allows them within the framework to confronttranscendental processes for his enterprise development of the globalization. Reports in Literature exist on motivations and benefits related to the implementation of Systems of Environmental Management under 14000 norm ISO [2] [3] [4] [5], of equal way exists bibliography on the impacts of the implementation of Systems of Management of Quality in much more specific aspects of the enterprise task [6] [7] [8]. As far as the Management of the Industrial Security and the Occupational Health many realised studies exist that demonstrate the impacts that have on the fulfillment of the objectives of the organizations [9] [10]. Nevertheless it is little what reports Literature on studies that much less include all the Organizational Systems of Management and in the Colombian reality. This article presents/ displays results obtained within the framework of the project of investigation -Y´Been of iffusion and use of the practical standards related to systems of organizational management in the MIPYMES of the Department of Cordoba-Y¡ executed by the Group of Investigation Engineering, Science and Technology ICT of the Faculty of Basic Sciences and Engineering’s of the University of Cordoba. The presented/displayed results orient to the evaluation of the degree of knowledge and organizational system application of management in the sector of drink and nutritional product elaboration (Code CIIU D150000) of the city of Montería, contributing to the generation of knowledge as far as the reach of the processes of normalization of the management, aspect of great importance as much for the regional economy as the national.